Regional Climate Services for Agriculture Project Presentation, and Demonstration and Discussion of Agricultural Maprooms: Launch Events at 44th Greater Horn of Africa Climate Outlook Forum - Mwesigwa, Jasper B.; Hansen, James; Dinku, Tufa; Owusu, Aisha (2016)
A joint collaborative initiative between ICPAC, CCAFS and IRI was launched publically through a series of presentations and side sessions at the 44th Greater Horn of Africa Climate Outlook Forum (GHACOF44) in Kampala, Uganda, on 30 August 2016. This initiative is part of the Climate Services for Africa Project, a three-year project funded by the United States Agency for International Development (USAID). The project is being implemented at ICPAC and is intended to roll out climate services in support of Agriculture and Food Security to ICPAC member states (all IGAD and EAC countries) with technical support from CCAFS and IRI. The overall goal of this initiative is to strengthen the capacity of ICPAC and that of ICPAC member countries to develop effective climate products and services for agriculture and food security, for the benefit of smallholder farmers.